Treatment and outcome of adult‐onset neuroblastoma. Issue 5 (6th April 2018) - Suzuki, Maya; Kushner, Brian H.; Kramer, Kim; Basu, Ellen M.; Roberts, Stephen S.; Hammond, William J.; LaQuaglia, Michael P.; Wolden, Suzanne L.; Cheung, Nai‐Kong V.; Modak, Shakeel
Abstract : Adult‐onset neuroblastoma is rare and little is known about its biology and clinical course. There is no established therapy for adult‐onset neuroblastoma. Anti‐GD2 immunotherapy is now standard therapy in children with high‐risk neuroblastoma; however, its use has not been reported in adults. Forty‐four adults (18–71 years old) diagnosed with neuroblastoma between 1979 and 2015 were treated at Memorial Sloan Kettering Cancer Center. Five, 1, 5 and 33 patients had INSS stage 1, 2, 3 and 4 diseases, respectively. Genetic abnormalities included somatic ATRX (58%) and ALK mutations (42%) but not MYCN ‐amplification. In the 11 patients with locoregional disease, 10‐year progression‐free (PFS) and overall survival (OS) was 35.4 ± 16.1% and 61.4 ± 15.3%, respectively. Among 33 adults with stage 4 neuroblastoma, 7 (21%) achieved complete response (CR) after induction chemotherapy and/or surgery. Seven patients with primary refractory neuroblastoma (all with osteomedullary but no soft tissue disease) received anti‐GD2 antibodies, mouse or humanized 3F8. Antibody‐related adverse events were similar to those in children, response rate being 71.4%. In patients with stage 4 disease at diagnosis, 5‐year PFS was 9.7± 5.3% and most patients who were alive with disease at 5 years died of neuroblastoma over the next 5 years, 10‐year OS being only 19.0 ± 8.2%. Patients who achieved CR after induction had superior PFS and OS ( p = 0.006, p = 0.031, respectively). Adult‐onset neuroblastoma appeared to have different biology from pediatric or adolescent NB, and poorer outcome. Complete disease control appeared to improve long‐term survival. Anti‐GD2 immunotherapy was well tolerated and might be beneficial. Abstract : What's new? Adult‐onset neuroblastoma is extremely rare, and little is known about its biology and clinical course. Anti‐GD2 immunotherapy is now incorporated into multi‐modal therapy in children with high‐risk neuroblastoma, but no standard treatment exists for adults. This report describes the clinical course, genomic features, prognostic factors, and treatment approaches including anti‐GD2 immunotherapy in the largest cohort of adults with neuroblastoma from a single institution. Adult‐onset neuroblastoma appeared to have different biology from pediatric or adolescent neuroblastoma, and poorer outcome regardless of stage at diagnosis. Complete disease control appeared to improve long‐term survival. Anti‐GD2 immunotherapy was well tolerated and might be beneficial.